Combining PCA with DEA to Improve the Evaluation of Project Performance Data: A Taiwanese Bureau of Energy Case Study. Issue 1 (February 2013) - Fu, Hsin-Pin; Ou, Jia-Ruey
This article proposes a new method of project performance evaluation, by which project performance data can be better understood. This article combines principal component analysis (PCA) and data envelopment analysis (DEA) to enhance the efficiency of decision-making units more accurately. The data used was based on energy projects promoted by the Bureau of Energy at the Ministry of Economic Affairs in Taiwan. The results of this article show that by combining PCA and DEA in evaluating the performance of energy projects, there was an improved evaluation of projects over simply using DEA data alone.